PELAKSANAAN PENYIDIKAN TINDAK PIDANA NARKOTIKA OLEH PENYIDIK POLRI DI WILAYAH HUKUM POLDA METRO JAYA (PERIODE 1 JANUARI 2023 S/D 31 DESEMBER 2023) - Yanto, Indri; Lumban Gaol, Selamat (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
The National Police plays a very important role in overcoming and enforcing the law related to narcotics crime cases. Investigators are members of the police who have duties and responsibilities in carrying out investigations into criminal acts. Investigators are responsible for gathering strong evidence to determine whether a criminal act has occurred and who is responsible for the act. In this research, we will discuss the Regulation of Narcotics Crimes and Their Investigations by Police Investigators in Indonesian Criminal Law and the Obstacles to Investigating Narcotics Crimes by Police Investigators in the Legal Area of Polda Metro Jaya for the Period 1 January 2023 to 31 December 2023. The legal research method used is normative juridical legal research methods supported by empirical data. Using a statutory approach and a conceptual approach obtained from primary, secondary and tertiary legal material sources. Regulation of Narcotics Crimes and Investigations by National Police Investigators in the Indonesian Criminal Law which is currently in force is regulated by Law Number 35 of 2009 concerning Narcotics and Investigation of Human Trafficking Crimes Based on the Indonesian Criminal Law which is currently in force is regulated in the Republic of Indonesia State Police Regulations Number 6 of 2019 concerning Criminal Investigations and on January 2 2026 regulated in Articles 609, 610 and 611 of Law Number 1 of 2023 concerning the Criminal Code. /d 31 December 2023 namely Limited Facilities and Infrastructure, Limited Human Resources for Investigators, Overlapping Authority with Other Institutions, Risks and Threats and Community Attitudes.